"I can't be the nurse I want to be": Counter-stories of moral distress in nurses' narratives of pediatric oncology caregiving. (March 2023) - Molinaro, Monica L.; Polzer, Jessica; Rudman, Debbie Laliberte; Savundranayagam, Marie
Abstract: As a term used in nursing and other health professions to describe when one is prevented by institutional constraints from pursuing the right course of action, moral distress has gained traction to examine the effects of restructuring on health and social care providers. Using a critical narrative methodology, this paper presents the counter-stories of nine pediatric oncology nurses in Ontario, Canada, whose stories illustrate the embeddedness of their caregiving and moral distress within institutional contexts that leave them stretched thin amongst multiple caregiving and administrative demands, and that limit their capacities to be the nurses they want to be. Informed by feminist philosophical theorizations of moral distress, we elucidate how the nurses' counter-stories: (i) re-locate the sources of their moral distress within institutional constraints that fracture their moral identities and moral relationships, and (ii) dis-locate dominant narratives of technological cure by ascribing value and meaning to the relational care through which they sustain moral responsibilities with patients and their families. By making visible the relational care that they find meaningful and that brings them in proximity to patients and families, these counter-stories assist nurses in restoring their damaged moral identities. This study demonstrates the power of identifying and mobilizing counter-stories in tracing and critically examining the conditions that structure nurses' experiences of moral distress. The findings add theoretical and empirical depth to contemporary understandings of moral distress and complement ongoing public discussion of burnout among nurses and other health care workers during the COVID-19 pandemic. These counter-narratives may act as resources for resistance among nurses, help to reduce the distance between management and health care workers, and catalyze changes in policy and practice so that nurses, and the full scope of their caregiving, are valued. Highlights: Counter-stories challenge dominant constructions of healthcare and caregiving. Moral distress is embedded in institutional constraints that fracture moral identities. Nurses' counter-stories assign meaning to relational care and moral responsibilities. Nurses' fractured moral identities are restored through counter-stories. Counter-stories act as narrative resources for resistance and resilience among nurses.